Efecto de 5 diferentes alimentos comerciales en la supervivencia, tamaño y susceptibilidad de Anopheles darlingi (Root, 1926) en condiciones de laboratorio - Huayanay Repetto, Anibal (2024)
The study was carried out between the months of May –December 2019, with the objective of knowing the effect of 5 different commercial foods on the survival, size and susceptibility of An. darling under laboratory conditions. Four trials were carried out for each food studied: Nutrafin, Puripaiche, LabDiet, Wiskas and Conejina. A total of 450 larvae were used for each trial, having a general total of 1800 larvae during the 4 trials. The foods with the shortest larval development time were LabDiet, Puripaiche and Nutrafin, wich lasts between 22 and 24 days. Regarding survival, all foods except Rabbit showed a rate greater than 70%. Wing size was statistically significant (p<0.05) in experimental infections with P. vivax. In conclusion, in this study commercial foods were shown to have an influence on larval development larval survival and wing size of the adult mosquito. However, there was no influence on the susceptibility of An. darling against P. vivax.